INFLUENCE OF ANTIHYPOTENSIVE DRUGS WITH A MODIFIED COMPOSITION IN THE TREATMENT OF GLAUCOMA ON THE COURSE OF DRY EYE SYNDROME - Fayzullaev Asilbek Iskandar ugli; Bilalov Bahodir Erkinovich; Narzikulova Kumri Islamovna (Scholar Express Journals, 2023)
Recently, the problem of the development of dry eye syndrome (DES) in patients with glaucoma has become particularly relevant. The main symptoms of DES are burning, redness, eye irritation, increased visual fatigue, and fluctuations in visual acuity during the day. In patients with glaucoma, the severity of symptoms correlates with the amount of antihypertensive drugs used, as well as the presence of a preservative in them.
Keywords: Dry eye; open-angle glaucoma